Analysis of the Effectiveness of Silicon Carbide Usage in the Jakarta Metro Traction System Using Matlab - Wijaya, Mohamad Angger Pamungkas; Irianto, Chairul Gagarin; Arifianto, Teguh (Journal of Railway Transportation and Technology, 2025)
Switching inverter technology for converting DC to AC using Insulated Gate Bipolar Transistors (IGBTs) has been implemented in the propulsion system of the Jakarta Metro. However, with advancements in power electronics, a newer technology—Silicon Carbide (SiC)—has emerged, offering the potential to reduce switching power losses by up to 30%. The effectiveness of this technology can be evaluated through simulations using MATLAB Simulink, enabling an assessment of its potential application in the Jakarta Metro system. By quantifying this efficiency gain, informed strategic decisions can be made regarding the adoption of SiC technology for DC to AC conversion, whether through the replacement of existing IGBT-based inverters or during the procurement of rolling stock for future phases. The evaluation will be conducted by simulating both existing IGBT parameters and proposed SiC device parameters under current traction motor operating conditions. This simulation aims to determine the output power required to drive the traction motor while maintaining alignment with the current train configuration. A comparative analysis of efficiency between the two technologies will form the basis of this thesis, providing insights into the feasibility and benefits of transitioning to SiC-based inverters for the Jakarta Metro.